DEFICIENCIES IN THE CONTROL ACTIVITIES OF THE MUNICIPAL SAVINGS BANK FROM NORTH OF PERU - Ramírez Osorio, Armanda (2015)
This paper is focused on an analysis of the deficiencies of control activities, the sixth component of Enterprise Risk Management: Integrated framework, COSO - ERM, identified as weaknesses in the Municipal Banks, according to the rating of risk agencies; and evaluating the effect that results in the management of the Muni-cipal Banks from Northern Peru during the 2008-2010 period. If we analyze the financial ratios of the Muni-cipal Banks, we note that some are not profitable, due to problems in business management. This research study determined that the problem is mainly related to management control, administrative controls and control of information processing, which adversely affect the management of the Municipal Banks, after it specifies the recommendation of the Good Corporate Governance practices implementation, as well as the process management system to ensure quality, conti-nuous and progressive improvement in these entities ́ organizations-subject of our study- and contribute to its strengthening.